Electrostatic force microscopy as a tool to estimate the number of active potential barriers in dense non-Ohmic polycrystalline SnO2 devices - Vasconcelos, J. S.; Vasconcelos, N. S. L. S.; Orlandi, Marcelo Ornaghi [UNESP]; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Barrado, C. M.; Leite, E. R. (American Institute of Physics (AIP), 2006)
In the present work, electroactive grain boundaries of highly dense metal oxide SnO2-based polycrystalline varistors were determined by electrostatic force microscopy (EFM). The EFM technique was applied to identify electroactive grain boundaries and thus estimate the amount of active grain boundary, which, in the metal oxide SnO2-based varistor, was calculated at around 85%, i.e., much higher than that found in traditional metal oxide ZnO-based varistors. The mean potential barrier height value obtained from the EFM analysis was in complete agreement with the values calculated from the C-V measurements, together with a complex capacitance plane analysis that validates the methodology proposed here. (c) 2006 American Institute of Physics.